Effect of Meditation in Prevention of Suicidal Deaths - K. Ravimuni; K. Usha Rani (Indian Journal of Forensic Medicine & Toxicology, 2021)
Stress is a feeling of emotional or physical tension. It can come from any event or thought that makes you feel frustrated, angry, or nervous. The period between childhood and adulthood is viewed as Adolescence. It is the period, where physiological and psychological maturity takes place. By nature, adolescents are sensitive, emotional, and temperamental and pass through a major transformation from childhood to adulthood involving a great physical, mental and emotional evolutionary process. Most of the students are stressful during the times of exams. Stress occurs while preparing and clearing the exams as one struggles to achieve the expected grade and mastering the content in a defined time. Raja Yoga meditation eases physiological and psychological stress and restores mental harmony if practiced on a regular basis; it is a compliment for promoting and maintaining physical, mental, and spiritual health. Heartfulness meditation used in this investigation is a simplified form of Raja Yoga where a practitioner meditates on the heart.